Adverse Childhood Experiences and Social Work: Relationship-based Practice Responses. (9th October 2020) - Frederick, John; Spratt, Trevor; Devaney, John
Abstract: Individuals with higher numbers of adverse childhood experiences (ACEs) have been found to be overrepresented amongst users of social services. This poses challenges for service providers in seeking ways to incorporate knowledge about ACEs in the calibration of service provision, and for social workers as to how they might use such knowledge in their day-to-day practice. The key contribution of this article is as a position piece that aims to map out a possible response to the ACEs evidence from social work. Practice needs to be informed by an understanding of the causes and consequences of trauma in the lives of individuals and groups. Short-term interventions based on proximal causes have resulted in a fundamental misunderstanding as to the aetiology of the problems experienced and to the types of interventions required to facilitate their amelioration. ACEs research offers a new understanding of how connecting trajectories are formed and maintained in ways that integrate biological, psychological and sociological concepts. In this article, we have made selective use of key texts and studies in the social work literature to illustrate how relationship-based social work may be appropriated and repurposed to align with interventions to mitigate the effects of ACEs.